2020
DOI: 10.1093/ntr/ntaa202
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cigarette Smoking, Smokeless Tobacco Consumption, and Use of both forms in Adolescents in South Asia: A Secondary Analysis of the Global Youth Tobacco Surveys

Abstract: Background Tobacco uptake in adolescents is associated with a range of predictors. We examined the predictors of cigarette smoking, smokeless tobacco (ST) consumption and use of both ST and cigarettes among adolescents in four South Asian countries. Methods We analysed the Global Youth Tobacco Surveys (GYTS) data for Bangladesh (2013), India (2009), Pakistan (2013), and Sri-Lanka (2015), using multinomial regression to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
10
21
1
Order By: Relevance
“…This smoking-friendly atmosphere exposes them to health risks and encourages them to start consuming tobacco. Consistent with other studies in the literature [8,33,34,47], we also observed significantly higher odds ratios of tobacco use among adolescents exposed to tobacco smoke compared to their counterparts. Exposure to smoking significantly increases the tobacco use risk three to seven times, indicating that the scope and enforcement of smoke-free policies were not enough.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This smoking-friendly atmosphere exposes them to health risks and encourages them to start consuming tobacco. Consistent with other studies in the literature [8,33,34,47], we also observed significantly higher odds ratios of tobacco use among adolescents exposed to tobacco smoke compared to their counterparts. Exposure to smoking significantly increases the tobacco use risk three to seven times, indicating that the scope and enforcement of smoke-free policies were not enough.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, after adjusting for inflation, in 2007, the cost of a pack of cigarettes was categorised as 'less than 64 TK', 'more than or equal to 64 TK' whereas in 2013, the categories were: 'less than or equal to 75 TK', 'between 76 to 200 TK', and 'more than 200 TK'. The selection of the factors associated with tobacco use was guided by related studies in the literature related to adolescent tobacco use [8,13,33,34].…”
Section: Factors Associated With Outcome Variablesmentioning
confidence: 99%
“…However, this association was no longer significant in the final model. This is in contrast to another study of LMIC settings which found that adolescents who were exposed to smoking in electronic media were more likely to be smokers [ 71 ]. Similar to the results of other studies [ 72 , 73 ], we found exposure to cigarette advertising in shops was a significant predictor of susceptibility in both countries after adjusting for sociodemographic factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, exposure to tobacco industry promotion was associated with tobacco product use (cigarette, non-cigarette tobacco products) among schoolgoing adolescents in the 22 African countries considered in our study. Our ndings are consistent with studies conducted elsewhere (45)(46)(47). Our nding may be attributed to the increased market in uence of the tobacco industry in many African countries(48).…”
Section: Discussionsupporting
confidence: 92%